2022
DOI: 10.1177/00033197211070908
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Utility of Mean Platelet Volume in Patients With Acute Coronary Syndrome: A Systematic Review With Meta-Analyses

Abstract: Mean platelet volume (MPV) is a hematological index that is routinely measured in clinical settings. Although many studies have been conducted to investigate the prognostic significance of MPV in acute coronary syndromes (ACS), the findings have been inconsistent. The goal of this study was to systematically review all current evidence on the association between admission MPV and clinical outcomes after ACS. PubMed, Scopus, Web of Science, and other databases were searched. The primary endpoints were major adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…In addition, studies have shown that MPV increases in diseases such as DM, acute coronary syndrome, stroke, preeclampsia, and hypercholesterolemia. [23][24][25][26] In a retrospective study of 1876 subjects, the relationship between MPV and plasma fasting glucose levels in the general population was investigated, and MPV was found to be higher in prediabetic patients than in normoglycemic subjects. Moreover, MPV and fasting glucose levels were found to be higher in patients with higher glucose levels than those with low glucose levels, not only in prediabetics but also among patients with normal fasting blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that MPV increases in diseases such as DM, acute coronary syndrome, stroke, preeclampsia, and hypercholesterolemia. [23][24][25][26] In a retrospective study of 1876 subjects, the relationship between MPV and plasma fasting glucose levels in the general population was investigated, and MPV was found to be higher in prediabetic patients than in normoglycemic subjects. Moreover, MPV and fasting glucose levels were found to be higher in patients with higher glucose levels than those with low glucose levels, not only in prediabetics but also among patients with normal fasting blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…MPV is a parameter used to measure the average size of platelets in the blood and has been extensively studied in recent years for its potential application in the assessment and prediction of CVD risk in patients with acute coronary syndrome. A meta-analysis of 41 studies involving over 33,000 participants found that elevated MPV levels were significantly associated with an increased risk of long-term mortality [ 5 ]. Furthermore, MPV was found to have a strong predictive value for future cardiovascular events, as observed in other studies of patients with varying degrees of CVD severity [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased MPV has been associated with an increased risk of major adverse cardiovascular events and mortality in patients with acute coronary syndrome as well as ischemic stroke and hypertension in the general population [ 5 , 6 ]. In patients with diabetes, increased MPV has been linked to poor glycemic control and an increased risk of diabetic complications [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 While several studies have been conducted to examine the prognostic value of MPV, there are inconsistent data around its utility in the prediction of ischemic outcomes. [5][6][7][8][9] Previously, we conducted a systematic review focused around the prognostic utility of MPV but only in acute coronary syndrome patients, 10 meanwhile another meta-analysis focused on only patients treated with percutaneous coronary intervention (PCI). 11 With new data available, we decided to update the systematic review and meta-analysis and broaden the population of interest.…”
Section: Introductionmentioning
confidence: 99%